Endogenous ROS-Mediated Covalent Immobilization of Gold Nanoparticles in Mitochondria: A “Sharp Sword” in Tumor Radiotherapy - Zhao, Yan; Feng, Yali; Li, Jiachen; Cui, Chaoxiang; Wang, Anna; Fang, Jing; Zhang, Yuqi; Ye, Shuyue; Mao, Qiulian; Wang, Xiaoyan; Shi, Haibin (ACS chemical biology, 2022)
Mitochondria as one of the key subcellular organelles have been well recognized as a promising druggable target and are closely associated with energy supply and various cellular functions. Realizing high accumulation and prolonged retention of radiosensitizers in the cellular mitochondria of tumors is an effective way to improve radiotherapeutic efficacy. Herein, we develop mitochondria-targeting and protein sulfenic acid (PSA)-reactive gold nanoparticles (dAuNP-TPP) that are fabricated by incorporating triphenylphosphine and 1,3-cyclohexanedione onto the surface of AuNPs (∼20 nm) to improve CT imaging and radiotherapeutic efficacy of tumors. Taking advantage of the specific mitochondrial targeting and PSA-mediated on-site covalent immobilization, this nanosystem shows significantly enhanced accumulation and retention in mitochondria with approximately 5.22-fold higher enrichment than nonimmobilizable AuNP-TPP. More notably, the covalent immobilization of dAuNP-TPP in cellular mitochondria could induce a dramatic reduction of ATP, leading to serious mitochondrial disruption, combined with the radiosensitization effect, in consequence achieving efficient radiotherapy of breast tumors in vivo. This subcellular organelle-targeted and immobilizable strategy may offer a valuable and universal tool for efficient tumor treatment.